Physicochemical characterization and quality of Dangshan pear wines fermented with different Saccharomyces cerevisiae. Issue 8 (4th June 2019) - Yang, Hua; Sun, Junyong; Tian, Tiantian; Gu, Hong; Li, Xiaomin; Cai, Guolin; Lu, Jian
Abstract: Three commercial yeasts strains, namely, Saccharomyces cerevisiae SY, DV10, and Drop Acid Yeast, were used for Dangshan pear wine fermentation. Monitoring main physical and chemical indexes and scoring comprehensive sensory characteristics to find a suitable yeast to produce Dangshan pear wine. The fermentation cycle of SY was short (15 days), and the SY‐fermented wine had a suitable sugar‐acid ratio, with a residual sugar content of 3.13 ± 0.05 g/L, total acid content of 3.40 ± 0.11 g/L, and ethanol content of 14.1 ± 0.27% (v/v). Additionally, 42 flavor compounds were detected in fermented Dangshan pear wine, and the total amount of flavor compounds was highest in the SY wine (2, 584.72 μg/L). Combined with the comprehensive sensory evaluation scores, these results suggest that Saccharomyces cerevisiae SY was the most suitable strain to produce Dangshan pear wine. Practical applications: In this study, we compared the physical and chemical indicators of pear wine brewed by different Saccharomyces cerevisiae in the process of fermentation and the final quality of pear wine products. It was concluded that the pear wine produced by Saccharomyces cerevisiae SY had good quality. The study found a strain suitable for the fermentation of pear wine and provided a theoretical basis for the industrial production of pear wine. Next, we can try to use Saccharomyces cerevisiae SY for large‐scale production of pear wine and try to sell it on the market.